HUBUNGAN TINGKAT PENGETAHUAN DAN SIKAP TERHADAP PERILAKU MASYARAKAT DALAM MENGOLAH SAMPAH DI DUSUN PADUKUHAN DESA SIDOKARTO KECAMATAN GODEAN KABUPATEN SLEMAN YOGYAKARTA - Mulasari, Surahma Asti (Jurnal Kesehatan Masyarakat (Journal of Public Health), 2012)
Background : Peoples habits in disposing waste by burning leaves or plastic waste has negative effect on health and also cause pollution. This is due to the lack of public knowledge in the processing of waste and the impact of the waste itself. This study aimed to determine the relationship between the level of knowledge and attitudes towards the behavior of the community in managing the daily garbage and waste management know that has been applied in the hamlet of Hamlet Village Sidokarto Godean Sleman district of Yogyakarta. Method : The study was an observational analytic cross sectional design. Sampling technique used was random sampling. The data was collected using questionnaires, with a total sample of 77 households. Analysis of data was using univariate and bivariate analysis with statistical test Fishers Exact Test. Results : The statistical result of the study, showed that as many as six heads of families or at (7.8%) had a level of knowledge that is not good in terms of waste management, and as many as 71 heads of households (respondent) or amount (92.2%) had a level of knowledge both in terms of waste manage-ment, while 7 households (respondent) or equivalent (9.1%) had a bad attitude in the process waste, and as many as 70 heads of households (respondent) or amount (90.9%) had a good attitude in process waste. Bivariate analysis to the level of knowledge on the behavior of the Hamlet Hamlet Village Si-dokarto Godean Sleman district of Yogyakarta in 2012 to process waste that is derived p <0.05 (p = 0.429) and RP = 1.246 (95% CI: 0.680 to 2.283). While the bivariate analysis for the behavioral attitude towards Hamlet Hamlet Village Sidokarto Godean Sleman district of Yogyakarta in 2012 to process waste that is derived p <0.05 (p = 0.088) and RP = 1.667 (95% CI: 1.141 to 2.434). Conclusion : There was no relationship between the level of knowledge of the behavior of people in the process waste in Hamlet Hamlet Village Sidokarto Godean Sleman district of Yogyakarta in 2012, and there is no relationship between attitude and behavior of people in the process waste in Hamlet Hamlet Village Sidokarto Godean Sleman district of Yogyakarta in 2012. Keywords: knowledge, attitude, behaviour, trash